2020
DOI: 10.33448/rsd-v9i8.5965
|View full text |Cite
|
Sign up to set email alerts
|

A Relação entre o Desempenho Cognitivo e a Dor em Cuidadores de Idosos

Abstract: Objetivo: avaliar o desempenho cognitivo de cuidadores de idosos com dor. Método: Trata-se de um estudo exploratório, não experimental de abordagem quantitativa com delineamento transversal e uma amostra não probabilística de 30 cuidadores de idosos. A coleta de dados foi realizada na sala de espera das consultas no Centro de Atenção à Saúde do Idoso e seus Cuidadores, Niterói-RJ. Foram utilizados instrumentos para o levantamento de dados como um questionário sociodemográfico para caracterização da amostra, a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Culturally, women are linked to home and family care functions, which explains the fact that most caregivers are female (DE ANDRADE, et al, 2020).…”
Section: Resultsmentioning
confidence: 99%
“…Culturally, women are linked to home and family care functions, which explains the fact that most caregivers are female (DE ANDRADE, et al, 2020).…”
Section: Resultsmentioning
confidence: 99%
“…If the caregivers' cognitive performance is impaired, the care activities for the older adults can be potentially compromised, such as preparing meals and handling medications, as well as identifying health-related problems. A study carried out in Niterói demonstrated that caregivers of older adults with dementia showed cognitive decline, especially in the memory domain 43 . Although the study was developed in the context of caring for older adults with dementia, it is noted that those data were similar to our study.…”
Section: Discussionmentioning
confidence: 99%